Prevalence of Staphylococcus aureus, Klebsiella spp., Escherichia coli and Pseudomonas spp. in some common Bangladeshi milk and dairy products - Paul, Partha; Al Hasan, Md. Zahid; Kumar, Arup; Chowdhury, Mohammad Hasan; Chowdhury, Md. Jayed; Purba, Nafisa Habib; Chakma, Moumita; Rahman, Shah Md. Ataur (Journal of Ecobiotechnology, 2020)
The study was done to isolate Klebsiella spp., Staphylococcus aureus, Escherichia coli & Pseudomonas spp. from raw milk, processed milk (powdered milk & ultra-high-temperature milk) and dairy products (mango milk, and ice cream). During 3 months’ time span of study, a total of ten samples were gathered where eight of the samples powdered milk (2), ultra-high-temperature milk (2), ice cream (2) & mango milk (2) were gathered from different places of Bangladesh & other 2 samples (raw milk) were collected from a cattle farm & individual households in & around Noakhali city. The samples were gathered under aseptic safety measures and were followed by plating on non-selective media (Nutrient broth) & selective media (Mannitol Salt Agar & Macconkey agar). The presumptive Klebsiella spp., Staphylococcus aureus, Escherichia coli & Pseudomonas spp. isolates were identified by biochemical tests. Analysis of the result discovered that out of a total of 10 samples; raw milk (2), processed milk i.e. powdered milk (2), ultra-high-temperature milk (2) and dairy products i.e. mango milk (2) and ice cream (2) resulted in the isolation of 8 isolates (2.5%) of S. aureus, (12.5%) of Klebsiella spp., (2.5%) of Pseudomonas spp. & (2.5%) of Escherichia coli. Results recommended a probability of potential public health threat of Staphylococcus aureus, Klebsiella spp., Escherichia coli & Pseudomonas spp. resulting from contamination of milk and dairy products with pathogenic microorganisms is mainly due to unhygienic practices and conditions in the handling, production, and processing.